Innovative Strategy to Meet the Challenges of the Future Digital Society - Bonnaud, Olivier (Advances in Technology Innovation, 2021)
Today, we are experiencing a societal revolution with the development of digital technologies, and it brings new challenges. Indeed, the number of connected objects, intelligent sensors and IoTs are increasing exponentially. The same goes for the resulting energy consumption. Beyond 2030, without a radical transformation of communication technologies and protocols, the digital world will be at an energy dead end. All these objects are physically realized with microelectronic devices and systems. This analysis of the microelectronics community has led the French government to recognize an electronics sector that is becoming a priority area of industrial policy. The Strategic Committee of this sector has proposed innovations applied to the entire digital chain including all facets of the microelectronics field and human skills and know-how. The technological and energy issues are thus presented, and the proposed solutions were addressed. They concern both technological and human aspects. This paper ends by giving examples of the implementation of innovative approaches which essentially include the electronic functions involved in connected objects and which are intended to bring the know-how of future actors in the field.